2012
DOI: 10.1161/atvbaha.111.239251
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase SHP2 Mediates Chronic Insulin-Induced Endothelial Inflammation

Abstract: Objective-Insulin promotes adhesion of leukocytes to the endothelium through increased expression of surface adhesion molecules. We determined whether src-homology domain-2-containing protein tyrosine phosphatase 2 (SHP2), a downstream effecter of insulin signaling, is involved in insulin-induced endothelial inflammation. Methods and Results-In human umbilical vein-derived endothelial cells, treatment with insulin (100 nmol/L) increased Tyr 542 phosphorylation, activity, and subsequently expression of SHP2. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 51 publications
2
33
1
Order By: Relevance
“…[4][5][6] In the current study, our qRT-PCR results demonstrated that administration of nor-NOHA abolished the differential expression of Icam1 in growing collaterals. These data are in accordance with results from Giri et al 31 showing that downregulation of arginase 2 in human umbilical vein endothelial cells abrogated leukocyte adhesion by blocking the expression of Icam1. Together these data indicate that arginase 2 activity in ECs is critical for perivascular macrophage accumulation, and hence effective arteriogenesis.…”
Section: Arginase Inhibition In Arteriogenesissupporting
confidence: 93%
“…[4][5][6] In the current study, our qRT-PCR results demonstrated that administration of nor-NOHA abolished the differential expression of Icam1 in growing collaterals. These data are in accordance with results from Giri et al 31 showing that downregulation of arginase 2 in human umbilical vein endothelial cells abrogated leukocyte adhesion by blocking the expression of Icam1. Together these data indicate that arginase 2 activity in ECs is critical for perivascular macrophage accumulation, and hence effective arteriogenesis.…”
Section: Arginase Inhibition In Arteriogenesissupporting
confidence: 93%
“…2 and 3), was also reported to greatly increase serum insulin levels (46,47) in a manner that is dependent on ␤ 3 -adrenergic receptor expression in white adipose tissue (47). At high concentrations, insulin can stimulate expression of adhesion molecules on the endothelium and promote leukocyte adhesion (48,49). Therefore, elevated cytokine or insulin levels may act alone or synergistically to activate the endothelium.…”
Section: Discussionmentioning
confidence: 98%
“…There is also a potential feedback loop consisting of several PTPs that are shown to directly or indirectly regulate the activity of NOSs, regulating either NOS tyrosine phosphorylation (coupled with changes in their activity) or transcriptional factors responsible for the NOS expression (6,12,16,25,35,36,38,44,65,77,85,87,91). The NOSs produce NO by a conversion of one of the terminal nitrogens of the guanidine group of L-arginine to NO, producing L-citrulline (37).…”
Section: Henebergmentioning
confidence: 99%
“…The mechanism involves protein kinase A and Akt (20,47). In response to insulin, endothelial SHP-2 is phosphorylated at one of its C-terminal tyrosines (Tyr 542 ), up-regulates its own expression in a p38 MAPK-dependent manner, and then up-regulates the expression and activity of arginase II, which leads to a decrease in cellular NO levels (36). Although the mechanisms are unclear, several indices suggest that at least some of the observed effects are mediated by the ability of SHP-2 to serve as a scaffold adaptor molecule and are unrelated to the SHP-2 phosphatase activity (20).…”
Section: Shp-2 Decreases No Productionmentioning
confidence: 99%